Off and out: the spaces for certification—offshore outsourcing in St Petersburg, Russia. - Feakins, Melanie (Environment & Planning A, 2007)
A study was conducted to investigate the emergence of two certification regimes—the International Standards Organization's ISO 9000 and Carnegie Mellon University's Capability Maturity Model (CMM)—as new forms of governance that shape understandings, perceptions, and strategies for gaining recognition within the outsourcing communities in the space of the offshore. Data were obtained from interviews carried out at 21 firms in the offshore software outsourcing sector in St. Petersburg, Russia. Findings indicated that certification is a form of economic globalization that is affecting microlevel economic activity through advocating specific forms of organization and structured work within companies. Findings suggested that the intersection of the international and global within the microspace of the firm in the post-Soviet offshore represents a power offshore that has contributed to the emergence of the conditions for certification as a form of governance. Findings are discussed in detail.